Total Plate dan Total Staphylococcus aureus pada Daging Di Pasar Tradisional Kecamatan Mulyorejo Surabaya - Mutiarasari, Nonie Olivia Adia; Harijani, Nenny; Rantam, Fedik Abdul; Raharjo, Dadik; Estoepangestie, Agnes Theresia Soelih; Handijatno, Didik (Universitas Airlangga, 2020)
This study aimed to evaluate the Total Plate Count and total Staphylococcus aureus count of beef sold in wet markets in Mulyorejo sub-district below the National Standard Indonesia (SNI 7388:2009) about maximum limit of microbial contamination in food or not. Total of twenty four samples of beef purchased from traditional markets of Tempurejo, Krempyeng Yamuri, Pacar Keling, and Menur in Mulyorejo sub-district Surabaya were examined by Total Plate Count using pour plate method. The sample was also cultured in Mannitol Salt Agar. The colony suspected to be S. aureus were taken for identification. The identification of S. aureus consists of isolation in Mannitol Salt Agar, Gram staining, catalase test, and coagulase test. Total plate count result showed that four samples were exceeding the National Standard of Indonesia SNI 7388:2009 or 1x106 CFU/g and the rest were below the maximum Total Plate Count in SNI. The highest Total Plate Count result was 1,9x106 CFU/g and the lowest was 7,8x104 CFU/g. The result of identification showed that 100% samples examined were contaminated by S. aureus with the highest result was 2,9x104 CFU/g and the lowest result was 4,3x103 CFU/g or exceeding the SNI 7388:2009.